THE EFFECT OF WORK ENGAGEMENT AND EMPLOYEE READINESS TO CHANGE ON ORGANIZATIONAL CHANGE WITH PERCEIVED ORGANIZATIONAL SUPPORT AS A MODERATING VARIABLE IN THE SHARIA BUSINESS UNIT OF PT. NUMUT BANK - Sukaria Sinulingga; Jauhari; Elisabet Siahaan (CV. Radja Publika, 2024)
Abstract This study aims to determine the effect of Work Engagement and Employee Readiness to Change on Organizational Change through Perceived Organizational Support as a moderating variable. This research is associative research and the type of data used is quantitative data. The data used is obtained from primary data and secondary data. The analysis method used is descriptive statistical analysis and structural equation modeling. The population and sample in this study amounted to 131 permanent employees in the Sharia Business Unit of PT Bank Sumut with the sampling used was proportional random sampling. The results of this study indicate that Work Engagement has a positive and yet insignificant effect on Organizational Change, Employee Readiness to Change has a positive and significant effect on Organizational Change, Perceived Organizational Support is unable to strengthen the influence of Work Engagement on Organizational Change, and Perceived Organizational Support is also unable to strengthen the influence of Employee Readiness